MAP Kinase Phosphatase-5 Deficiency Protects Against Pressure Overload-Induced Cardiac Fibrosis - Zhong, Chao; Min, Kisuk; Zhao, Zhiqiang; Zhang, Cheng; Gao, Erhe; Huang, Yan; Zhang, Xinbo; Baldini, Margaret; Roy, Rajika; Yang, Xiaofeng; Koch, Walter J.; Bennett, Anton M.; et al. (Frontiers in Immunology, 2021)
Cardiac fibrosis, a pathological condition due to excessive extracellular matrix (ECM) deposition in the myocardium, is associated with nearly all forms of heart disease. The processes and mechanisms that regulate cardiac fibrosis are not fully understood. In response to cardiac injury, macrophages undergo marked phenotypic and functional changes and act as crucial regulators of myocardial fibrotic remodeling. Here we show that the mitogen-activated protein kinase (MAPK) phosphatase-5 (MKP-5) in macrophages is involved in pressure overload-induced cardiac fibrosis. Cardiac pressure overload resulting from transverse aortic constriction (TAC) leads to the upregulation of Mkp-5 gene expression in the heart. In mice lacking MKP-5, p38 MAPK and JNK were hyperactivated in the heart, and TAC-induced cardiac hypertrophy and myocardial fibrosis were attenuated. MKP-5 deficiency upregulated the expression of the ECM-degrading matrix metalloproteinase-9 (Mmp-9) in the Ly6Clow (M2-type) cardiac macrophage subset. Consistent with in vivo findings, MKP-5 deficiency promoted MMP-9 expression and activity of pro-fibrotic macrophages in response to IL-4 stimulation. Furthermore, using pharmacological inhibitors against p38 MAPK, JNK, and ERK, we demonstrated that MKP-5 suppresses MMP-9 expression through a combined effect of p38 MAPK/JNK/ERK, which subsequently contributes to the inhibition of ECM-degrading activity. Taken together, our study indicates that pressure overload induces MKP-5 expression and facilitates cardiac hypertrophy and fibrosis. MKP-5 deficiency attenuates cardiac fibrosis through MAPK-mediated regulation of MMP-9 expression in Ly6Clow cardiac macrophages.